Patient and health service factors associated with enrollment in a multidisciplinary pain rehabilitation program: a retrospective cohort study - Michael A. Bushey; Michael A. Bushey; Lindsay G. Flegge; Lindsay G. Flegge; Melissa Melendez; Elizabeth K. Harris; Flora M. Hammond; Flora M. Hammond (Frontiers in Pain Research)
IntroductionDespite multidisciplinary pain rehabilitation programs (PRPs) being well-established as an effective treatment for chronic pain, the existence of such programs has been declining across the United States over recent decades.ObjectiveThis study aims to identify factors associated with enrollment in a three-week, intensive outpatient PRP.MethodsThis is a retrospective cohort study of all patient visits to a multidisciplinary pain evaluation clinic in 2023. The cohort was divided into those who did and did not subsequently enroll in a PRP program. Health service, demographic, and patient-reported outcome measures were compared between groups; continuous variables by independent samples Student's T-tests and categorical variables by chi-squared tests.ResultsOf the 335 patients who had an evaluation in 2023, 48 went on to enroll in PRP (PRP-Yes group), and 287 did not (PRP-No group). Compared to PRP non-enrollers, the PRP-enrollers were more likely to have had a mental health (94% vs. 52%, p < .001) and physical therapy (94% vs. 48%, p < .001) assessment as part of their evaluation, had shorter lag times between their initial referral and medical evaluation [mean (SD) 43.5 (28.9) vs. 57.7 (41.7), p = .024], and had significantly greater anxiety, PTSD symptoms, somatic symptoms, and insomnia. Additionally, referral source, medical provider, and physical therapy provider seen differed significantly between PRP-enrollers and non-enrollers. PRP enrollment was not predicted by demographic variables including race, payer-type, or distance from the clinic.DiscussionBoth personal and systemic factors were identified to be associated with enrollment in a three-week multidisciplinary PRP. These findings highlight variables worth considering for clinical and research programs looking to increase PRP enrollment.